PENGARUH PELATIHAN KERJA, DISIPLIN KERJA, GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN GAYA KEPEMIMPINAN TRANSAKSIONAL TERHADAP KINERJA PEGAWAI (Studi pada Dinas Koperasi dan UKM Provinsi Jawa Tengah) - Hanif Maesaroh, 15.05.51.0374; Rahayuningsih, sri (Students' Journal of Economic and Management, 2019)
This study aims to analyze the effect of job training, work discipline, transformational leadership style, and transactional leadership style on the performance of Central Java Province Cooperative and Small and Medium Enterprises staff. The type of data used is primary data, namely data obtained directly from the original source in the form of a questionnaire. The population of this study were employees of the Central Java Provincial Office of Cooperatives and Small and Medium Enterprises. Sampling was done by purposive sampling technique with a total sample of 73 respondents. The collected data were analyzed using factor analysis to test the validity of question items, reliability testing using Cronbach alpha, and hypothesis testing using multiple linear regression. The test results obtained that there is a positive and significant effect of job training on employee performance, there is a positive and significant influence of work discipline on employee performance, there is a positive and significant influence of transformational leadership style on employee performance, and there is a positive and significant effect of transformational leadership style on employee performance.